Gaming and the Arts of Storytelling - Jayemanne, Darshana (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book examines the notion of storytelling in videogames. This topic allows new perspectives on the enduring problem of narrative in digital games, while also opening up different avenues of inquiry. The collection looks at storytelling in games from many perspectives. Topics include the remediation of Conrad's Heart of Darkness in games such as Spec Ops: The Line; the storytelling similarities in Twin Peaks and Deadly Premonition, a new concept of 'choice poetics'; the esthetics of Alien films and games, and a new theoretical overview of early game studies on narrative